2010
DOI: 10.1590/s1516-31802010000600007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between infectious agents for vulvovaginitis and skin color

Abstract: CONTEXT AND Objective: Many factors influence occurrences of vulvovaginitis. The aims here were to assess skin color and age-related differences in the vaginal flora and occurrences of vulvovaginitis. DESIGN AND SETTING:Cross-sectional study; tertiary referral hospital (Universidade Federal do Triângulo Mineiro, Uberaba). METHODS:Healthy women who underwent routine outpatient gynecological assessments were assessed for vulvovaginitis and vaginal flora and then divided into whites (n = 13,881) and nonwhites (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
3
0
3
Order By: Relevance
“…Research reported in the literature has demonstrated an association between skin color, pH, and genital infections. [ 13 ] However, the participation of other variables, biological (race/ethnicity and genetic polymorphisms[ 14 ]) or socioeconomic and cultural, such as hygiene, sexual practices, and other activities that could transmit sexual maladies require more investigation. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Research reported in the literature has demonstrated an association between skin color, pH, and genital infections. [ 13 ] However, the participation of other variables, biological (race/ethnicity and genetic polymorphisms[ 14 ]) or socioeconomic and cultural, such as hygiene, sexual practices, and other activities that could transmit sexual maladies require more investigation. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The normal vaginal microbiota is predominantly comprised of lactobacilli (bacilli Döderlein hosting), which promote the proper acidity of the vaginal environment (~ pH 4.5); this hinders the proliferation of most microorganisms that can eventually be pathogenic. Despite this balance, several factors contribute to the colonization of vagina by Candida species, sometimes favoring the onset of symptoms or the occurrence of asymptomatic infections 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that vulvovaginal candidiasis (VVC) is the second most frequent cause of vaginal symptoms, representing 17 to 39% of the cases, and bacterial vaginosis (BV) corresponding to about 50% 2 . Around 75% of women present with vaginal discomfort at any stage of life, and among these cases, 50% have other episodes of VVC and 5% have recurrent vulvovaginal candidiasis (CVVR).…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura atual, podemos classificar as comunidades vaginais em relação aos grupos étnicos (Tab 1) [21] [22] [44] [51]. A estrutura de microbiota vaginal de ascendência europeia e asiática tende a ser colonizado pelo CSTs I ou III, assim sendo historicamente a microbiota mais "estável", visto que esses Lactobacillos crispatus promova grande síntese de ácido lático e peroxido de oxigênio, deixando o pH da região mais baixo [16] [20] [36] [37] [45] [51].…”
Section: Padrões Sociais/ éTnicosunclassified